Vacuolar sorting receptors (VSRs) and secretory carrier membrane proteins (SCAMPs) are essential for pollen tube growth - Wang, Hao; Hillmer, Stefan; Robinson, David G. (The plant journal, 2009)
Vacuolar sorting receptors (VSRs) are type-I integral membrane proteins that mediate biosynthetic protein traffic in the secretory pathway to the vacuole, whereas secretory carrier membrane proteins (SCAMPs) are type-IV membrane proteins localizing to the plasma membrane and early endosome (EE) or trans-Golgi network (TGN) in the plant endocytic pathway. As pollen tube growth is an extremely polarized and highly dynamic process, with intense anterograde and retrograde membrane trafficking, we have studied the dynamics and functional roles of VSR and SCAMP in pollen tube growth using lily (Lilium longiflorum) pollen as a model. Using newly cloned lily VSR and SCAMP cDNA (termed LIVSR and LISCAMP, respectively), as well as specific antibodies against VSR and SCAMP1 as tools, we have demonstrated that in growing lily pollen tubes: (i) transiently expressed GFP-VSR/GFP-LIVSR is located throughout the pollen tubes, excepting the apical clear-zone region, whereas GFP-LISCAMP is mainly concentrated in the tip region; (ii) VSRs are localized to the multivesicular body (MVB) and vacuole, whereas SCAMPs are localized to apical endocytic vesicles, TGN and vacuole; and (iii) microinjection of VSR or SCAMP antibodies and LlVSR small interfering RNAs (siRNAs) significantly reduced the growth rate of the lily pollen tubes. Taken together, both VSR and SCAMP are required for pollen tube growth, probably working together in regulating protein trafficking in the secretory and endocytic pathways, which need to be coordinated in order to support pollen tube elongation.